Hakam (State of Selangor) Rules 2014: An overview - Abdul Hak, Nora; Abdul Syahid Sowell, Sarafuddin (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
In 2014, Hakam Rules was introduced by the State of Selangor with the aim to help estranged Muslim couples to resolve their quarrels with the help of hakam. Under this Rules, the Syariah Court could grant a divorce to a woman even if her husband is uncooperative. Divorce by hakam is a better alternative than forcing the wife to endure the protracted trial of fasakh or ta’liq. Selangor is the first state to effect this change and it is hoped that other states will follow suit. Thus, it is the aim of this paper to discuss the provision on marital dispute resolution by means of hakam as provided for under the Hakam Rules 2014 of Selangor. Firstly, the paper deals with the provision on hakam under the Islamic Family Law (State of Selangor) Enactment 2003. The critical analysis focuses on section 47 (5) to (17) and, specifically of section 48 of the Enactment. These relevant provisions are analysed against the background of the principles and rules of tahkim (arbitration) as deliberated in the sources of syariah i.e., Qur’an, Sunnah, Ijma’, Qiyas and other secondary sources of shariah. In this paper, Islamic legal research methodology is adopted. It involves a study of the relevant literature on the law (fiqh), the Qur’anic exegesis, the traditions of the Prophet Muhammad (hadith) and opinions of the four major schools of shariah relating to the principles and rules of tahkim/hakam. Finally, suggestions and recommendations to further improve the current practice and provisions on hakam are discussed in this paper.